New Insights Into the Role of Autophagy in Liver Surgery in the Setting of Metabolic Syndrome and Related Diseases - Álvarez-Mercado, Ana Isabel; Rojano-Alfonso, Carlos; Micó-Carnero, Marc; Caballeria-Casals, Albert; Peralta, Carmen; Casillas-Ramírez, Araní (Frontiers in Cell and Developmental Biology, 2021)
Visceral obesity is an important component of metabolic syndrome, a cluster of diseases that also includes diabetes and insulin resistance. A combination of these metabolic disorders damages liver function, which manifests as non-alcoholic fatty liver disease (NAFLD). NAFLD is a common cause of abnormal liver function, and numerous studies have established the enormously deleterious role of hepatic steatosis in ischemia-reperfusion (I/R) injury that inevitably occurs in both liver resection and transplantation. Thus, steatotic livers exhibit a higher frequency of post-surgical complications after hepatectomy, and using liver grafts from donors with NAFLD is associated with an increased risk of post-surgical morbidity and mortality in the recipient. Diabetes, another MetS-related metabolic disorder, also worsens hepatic I/R injury, and similar to NAFLD, diabetes is associated with a poor prognosis after liver surgery. Due to the large increase in the prevalence of MetS, NAFLD, and diabetes, their association is frequent in the population and therefore, in patients requiring liver resection and in potential liver graft donors. This scenario requires advancement in therapies to improve postoperative results in patients suffering from metabolic diseases and undergoing liver surgery; and in this sense, the bases for designing therapeutic strategies are in-depth knowledge about the molecular signaling pathways underlying the effects of MetS-related diseases and I/R injury on liver tissue. A common denominator in all these diseases is autophagy. In fact, in the context of obesity, autophagy is profoundly diminished in hepatocytes and alters mitochondrial functions in the liver. In insulin resistance conditions, there is a suppression of autophagy in the liver, which is associated with the accumulation of lipids, being this is a risk factor for NAFLD. Also, oxidative stress occurring in hepatic I/R injury promotes autophagy. The present review aims to shed some light on the role of autophagy in livers undergoing surgery and also suffering from metabolic diseases, which may lead to the discovery of effective therapeutic targets that could be translated from laboratory to clinical practice, to improve postoperative results of liver surgeries when performed in the presence of one or more metabolic diseases.